INFLUENCE OF PREPARATIONS ON BIOLOGICAL PROCESSES OF ALLUVIAL SOILS OF IRRIGATED MEADOW IN BUKHARA OASIS - Mamasolieva, Malika; Gafurova, Laziza; Sharipov, Odiljon (Innovatsion texnologiyalar, 2024)
Today, a number of developed countries use silicon-containing preparations to improve the relationship between soil and plants, thereby achieving high productivity. Improving the biological properties of soil means improving the plant immune system, the process of forming reactions to stress and high productivity. Soil microorganisms play an important role in this process. This article examines the effect of silicon-containing preparations on improving the biological properties of irrigated pasture-alluvial soils. The influence of the preparations Aminoside-Aton, Aminoside-Silicon and Bionitrogen on seasonal changes in the activity of soil microorganisms was studied.